Contesting the Portrayal of Beauty As It is in Music Videos: A Semiotic Analysis of the Video of Yura Yunita-Tutur Batin - Dini Okta Lamdia; Anang Dwi Santoso; Rindang Senja Andarini (MUWAZAH : jurnal kajian gender, 2023)
Recently, "beauty as it is" has been featured in commercials for beauty products, movies, and music videos. This concept arose from a lengthy conversation about normative beauty, according to which a beautiful lady is always characterized by having fair complexion, straight hair, and a fresh face. This study, in response to these developments, challenges if, in the manufacture of "beauty as it is," capitalists continue to use women's bodies as commodities instruments, not only beauty and sexiness but also women's flaws and powerlessness. In more detail, this study employs a critical paradigm, Roland Barthes' semiotic analysis, and Stuart Hall's representation theory to deconstruct the denotation, connotation, and myths that form in the music video for Yura-Yunita-Tutur Batin. Findings of this study indicates that women who do not adhere to beauty norms would face prejudice. The prevalence of beauty privilege is damaging not just to women who are far from beauty standards, but also to gorgeous women, who are regarded as having beauty capital alone. The female body is once again objectified in this video. Women's physical appearances are shown in a variety of ways by expressing themselves as they are, but the music video nonetheless builds conventional standards of beauty. The body positivity campaign resulted in poisonous body positivity, and women supporting women was only carried out by women with the same physical issues, while the rest depicted women dropping other women.